Development of Flipbook-Based E-Modules on Class XI Construction Cost Estimation Subjects - Putri Nur'aini Hilaliyah; Tri Kuncoro; Isnandar Isnandar; Andri Setiyawan (Jurnal Pendidikan Teknik Sipil, 2024)
Background: This research is motivated by the problems faced by grade XI DPIB students at SMK Negeri 3 Boyolangu, namely the lack of availability of learning media and students' difficulties in determining the basic formula for calculating the volume of building construction. The purpose of this research and development is to produce flipbook-based e-module media on class XI Construction Cost Estimation Subjects; to find out its feasibility and practicality based on experts and students; and to find out the effectiveness of using flipbook-based e-modules in learning.Methods: The method used is research and development (R&D) by applying the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection instruments using preliminary instruments (interviews and observations), validation questionnaires include media experts and material experts, student response questionnaires, and cognitive test questions (pre-test and post-test).Results: (1) The results of flipbook-based e-module products have advantages in ease of use and a variety of features, including: interactive buttons, backsound for flipping, image pop-ups, youtube video pop-ups, web hyperlinks, and quiz games, so as to be able to present a clearer visualization of the material and encourage student enthusiasm for learning. (2) Media eligibility obtained a score from media experts of 96% and from material experts of 93%, this score is included in the category of very feasible. While the practicality of the media was obtained from the user response questionnaire, obtaining an average percentage of 88% with very practical criteria. (3) The effectiveness of the use of media in learning obtained an N-Gain Score of 0.63 with the criterion "moderate".Conclusion: Based on the test results, it is concluded that the developed flipbook-based e-module media is effectively used to improve student understanding.